Trace element distribution in the hair of some sickle cell anemia patients and controls - Oluwole, A F; Asubiojo, O I; Adekile, A D; Filby, R H; Bragg, A; Grimm, C I (Biological trace element research, 1990)
Hair samples of some young sickle cell anemia (SCA) and control patients in Nigeria were analyzed for 12 elements, viz, Se, Hg, Cr, Fe, Zn, Co, Cu, Br, As, Sb, Na, and Sc, using Instrumental Neutron Activation Analysis (INAA). With the exception of Cu, which was found to be significantly higher in the hair of SCA patients (at the 0.05 level of the t-test), there were generally no significant differences in elemental concentrations within the two groups. A preliminary study of the elemental contents of the fingernails of the same subjects showed a higher abundance of most of the elements in nail than in hair. These preliminary results were compared with similar studies from some other parts of the world.